Enhancing Students’ Creative Thinking through Project-Based Physics E-Modules - Rahma Diani; Yuberti Yuberti; Adek Erni Kurnia; Arti Hadap (Smart Society, 2024)
The creative thinking ability of students in physics learning is still relatively low, especially because the strategies, methods or learning media are less varied and do not involve students actively in the learning process. This study aims to determine the effect of project-based learning physics e-modules on students' creative thinking abilities. This study is a pre-experimental study using a one group pretest-posttest design. The sample consisted of 90 students selected using the purposive sampling technique. This project-based learning physics e-module product is effective in improving students' creative thinking abilities as seen from the results of the n-gain test to the three schools, an average n-gain of 0.71 was obtained in the high category. Based on the interpretation of the effectiveness of the n-gain value of 71% obtained, it is classified into the fairly effective category. And seen from the hypothesis test, it produces sig. less than 0.05. This study has implications for the effectiveness of students' creative thinking abilities because of the influence of project-based learning physics e-modules.